Cytokines in Liver Cirrhosis (Their Importance in Assessing Activity and Decompensation) - G. K. Mirodzhov; S. D. Pulatova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: studying the role of pro-inflammatory and anti-inflammatory cytokines in the pathogenesis of liver cirrhosis progression.Materials and methods. The material of the study was the data of clinical-instrumental, biochemical, virological studies of 109 patients with liver cirrhosis of various etiologty, who were hospitalized in the clinic of the Institute of Gastroenterology (Dushanbe, Republic of Tajikistan). The diagnosis of the underlying disease was established according to the clinical recommendations of the Russian Society for the Study of the Liver and the Russian Gastroenterological Association for the diagnosis and treatment of liver fibrosis and cirrhosis and their complications (2021); decompensated liver cirrhosis was established according to the 1996 Child — Pugh classification. The age of the patients ranged from 17 to 79 years (36.9 ± 0.8 years), there were 55 men and 54 women.Results. Among the examined patients, compensated liver cirrhosis (Class A) according to Child — Pugh was detected in 18 persons, subcompensated (Class B) — in 14, decompensated (Class C) — in 77. The study of the content of pro-inflammatory and anti-inflammatory cytokines in the blood serum of patients with Class A liver cirrhosis showed, that levels of tumour necrosis factor alpha (TNF-α), interleukin-2, interleukin-6 were statistically higher compared to healthy individuals, while the concentration of anti-inflammatory interleukin-10 was lower (30.7 ± 4.7 pg/mL) in comparison with the control group. In patients with Class B liver cirrhosis, the level of TNF-α increased to 75.0 ± 4.5 pg/mL (p < 0.001), interleukin-2 — to 328.7 ± 23.9 pg/mL (p < 0.05), and interleukin-6 — to 95.4 ± 7.7 pg/mL (p < 0.001). Serum interleukin-10 decreased compared with the control group (23.1 ± 2.8 pg/mL; p > 0.05). At the decompensated stage of Class C cirrhosis, a huge release of pro-inflammatory cytokines occurs — the content of TNF-α increases by 80 times, of interleukin-2 — by more than 60 times, аs for interleukin-10, its content is progressively reduced.Conclusion. In liver cirrhosis, there is a significant disruption in the synthesis of pro-inflammatory cytokines, which is manifested by a sharp increase in the content of TNF-α, interleukin-2 and interleukin-6. High levels of proinflammatory cytokines in blood serum in liver cirrhosis correlate with the activity and degree of decompensation, which indicates their important role in the pathogenesis and progression of the pathological process.